2018
DOI: 10.1155/2018/7267920
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Natural Health Products Especially Papaya Leaf Extract and Dandelion Root Extract in Previously Untreated Chronic Myelomonocytic Leukemia

Abstract: Chronic myelomonocytic leukemia (CMML) is a clonal hematopoietic disorder which shares clinical and morphological features of myelodysplastic syndrome and myeloproliferative neoplasms. Conventional therapeutic options include hydroxyurea, hypomethylating agents, and systemic chemotherapy, which are all palliative measures and are associated with potential side effects. Allogeneic hematopoietic cell transplantation is the only curative option. Natural health products such as papaya leaf extract and dandelion ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…This foundational step is integral to determining optimal dosages and duration of administration, thereby establishing a solid groundwork for subsequent human trials [ 27 ]. In the current study, the dosages chosen were guided by existing human usage patterns for C. papaya leaf extract, which has previously been employed as a dietary supplement [ 37 ]. In humans, the daily dosage for this extract ranges from 1 to 50 g, which translates into a daily intake of 17 to 833 mg for an average 60 kg male [ 5 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This foundational step is integral to determining optimal dosages and duration of administration, thereby establishing a solid groundwork for subsequent human trials [ 27 ]. In the current study, the dosages chosen were guided by existing human usage patterns for C. papaya leaf extract, which has previously been employed as a dietary supplement [ 37 ]. In humans, the daily dosage for this extract ranges from 1 to 50 g, which translates into a daily intake of 17 to 833 mg for an average 60 kg male [ 5 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies have shown that dandelions have antimicrobial, antiviral, anticancer, antioxidant, anti-inflammatory, and anti-allergic effects ( He et al, 2011 ; Ovadje et al, 2011 ; Ovadje et al, 2012 ; Qian et al, 2014 ; Wang, 2014 ; Ma et al, 2015 ; Ovadje et al, 2016 ; Jedrejek et al, 2017 ; Rehman et al, 2017 ; Ding and Wen, 2018 ; Liu et al, 2018 ; Rahmat and Damon, 2018 ). Extract from Dandelion: ethyl acetate extract (EAED).…”
Section: The Effect Of Traditional Chinese Therapy On Cholinergic Ant...mentioning
confidence: 99%
“…In addition, it has many pharmacological effects. Modern pharmacological studies show that the properties of dandelion include antibacterial [ 9 , 10 ], antiviral [ 11 ], anticancer [ 12 16 ], antioxidant [ 17 ], anti-inflammatory [ 18 20 ], and antiallergic functions. In terms of the alleviation of airway inflammation, a distinctive feature of asthma, it has been reported that the organic acid components of TMHM can improve lipopolysaccharide-induced histopathological damage to tracheal tissues [ 21 ] and reduce lipopolysaccharide-induced inflammation in normal human bronchial epithelial cells [ 22 ], which could be beneficial for the treatment of acute tracheobronchitis.…”
Section: Introductionmentioning
confidence: 99%